An integrated electrolysis – electrospray – ionization antimicrobial platform using Engineered Water Nanostructures (EWNS) for food safety applications. (March 2018) - Vaze, Nachiket; Jiang, Yi; Mena, Lucas; Zhang, Yipei; Bello, Dhimiter; Leonard, Stephen S.; Morris, Anna M.; Eleftheriadou, Mary; Pyrgiotakis, Georgios; Demokritou, Philip
Abstract: Engineered water nanostructures (EWNS) synthesized utilizing electrospray and ionization of water, have been, recently, shown to be an effective, green, antimicrobial platform for surface and air disinfection, where reactive oxygen species (ROS), generated and encapsulated within the particles during synthesis, were found to be the main inactivation mechanism. Herein, the antimicrobial potency of the EWNS was further enhanced by integrating electrolysis, electrospray and ionization of de-ionized water in the EWNS synthesis process. Detailed physicochemical characterization of these enhanced EWNS (eEWNS) was performed using state-of-the-art analytical methods and has shown that, while both size and charge remain similar to the EWNS (mean diameter of 13 nm and charge of 13 electrons), they possess a three times higher ROS content. The increase of the ROS content as a result of the addition of the electrolysis step before electrospray and ionization led to an increased antimicrobial ability as verified by E. coli inactivation studies using stainless steel coupons. It was shown that a 45-min exposure to eEWNS resulted in a 4-log reduction as opposed to a 1.9-log reduction when exposed to EWNS. In addition, the eEWNS were assessed for their potency to inactivate natural microbiota (total viable and yeast and mold counts), as well as, inoculated E. coli on the surface of fresh organic blackberries. The results showed a 97% (1.5-log) inactivation of the total viable count, a 99% (2-log) reduction in the yeast and mold count and a 2.5-log reduction of the inoculated E. coli after 45 min of exposure, without any visual changes to the fruit. This enhanced antimicrobial activity further underpins the EWNS platform as an effective, dry and chemical free approach suitable for a variety of food safety applications and could be ideal for delicate fresh produce that cannot withstand the classical, wet disinfection treatments. Highlights: An enhancement was made in the nanotechnology based EWNS platform for disinfection. A novel Enhanced Engineered Water Nanostructure (eEWNS) technology was developed. These eEWNS were tested against E. coli and significant reduction was achieved. Blackberries, a delicate produce, were treated with eEWNS. The results indicate the promise of this technology for food safety applications.